ANALISIS GAYA BAHASA PADA MEDIA BERITA ONLINE LIPUTAN 6.COM - Alan; Hartati (JURNAL ILMIAH NUSANTARA, 2025)
The problem in this study is what language styles are used in the online news media on Liputan6.com. The expected benefits of this research result can provide the development of scientific insight into Indonesian literature. This type of research is content analysis research, the method used is a qualitative method. The application of this qualitative method is descriptive, meaning the resulting data is in the form of words in the form of quotations. The source of this research is news published in the online mass media Liputan 6.Com edition, May 2025. The data collection technique used is document review technique. This research data was analyzed using a sociolinguistic approach. It was concluded that the language styles found in the online news media Liputan6.com, which were found by the researcher were divided into several parts, namely, metonymy, metaphor, epithet, synecdoche, personification, assonance, and antithesis.